Six Sigma Applied to Healthcare: A Global Scientometrics Analysis of Health Services Quality Improvement Research - Yorjanis Galván-Pérez; Matilde Herrera-Polo; David A. Hernández-Páez; Dionicio Neira Rodado; Katherinne Salas-Navarro; Alba Marina Rueda-Olivella; Tulia Beltrán-Venegas; Ivan David Lozada-Martinez; Patricia Delgado (Health Services Insights)
Aim: To provide a comprehensive scientometrics analysis of Six Sigma research in healthcare, a field gaining momentum due to its capacity to address missed improvement opportunities and inefficient cost-control strategies across global health systems. Design: A cross-sectional mixed-methods study combining quantitative research and health metrics with thematic content analysis to explore trends and research patterns. Methods: The study analyzed publications indexed in PubMed, Scopus, Web of Science, SciELO, and KCI, using thematic mapping techniques through term co-occurrence networks and cluster analysis. Also, correlation analysis with healthcare quality indicators and global health metrics were executed. Results: A total of 883 publications were analyzed. (1) Geographical analysis showed 70.8% from high-income countries and 0.7% from low-income countries. (2) Thematic clusters were centered on hospital applications and patient safety. (3) Temporal trends revealed an increasing focus on “big data” and “health innovation.” (4) Strong correlations were found between publication output and health/research expenditure ( P  < .01 for all cases); negative associations emerged with out-of-pocket expenditures and researcher density in low-income settings. Conclusions: Findings provide a roadmap for aligning global research priorities and highlight the need for inclusive strategies that build research capacity and foster context-sensitive applications of Six Sigma in healthcare.